IMPLEMENTATION OF AMBIENT CONDITION, SPATIAL LAYOUT AND FUNCTIONALITY AND SIGN SYMBOLS AND ARTIFACTS IN IMPROVING CUSTOMER SATISFACTION AND CUSTOMER LOYALTY JANJI JIWA & JIWA TOAST - Ahmad Azmi (Institute of Computer Science (IOCS), 2021)
In the current era of globalization, it encourages intense competition in all areas of business, especially coffee shops which are growing rapidly. The development of trends in a coffee shop with certain characteristics triggers intense competition among operators of coffee shops. In terms of creating a competitive advantage, coffee shops must also focus on customer satisfaction. With the new habits, people are currently changing old habits to meet their needs, one of which is the demand for food tends to fast-food restaurants, cafes, or coffee shops. This research is a survey of Serious Janji Jiwa & Jiwa Toast consumers in Medan. The sampling technique uses accidental sampling of 180 people. Data analysis use path analysis. The data were processed using Smart PLS, The results of this study indicate that the ambient condition, spatial layout and functionality, and sign of symbols and artifacts have a significant on customer satisfaction and customer loyalty